2019
DOI: 10.3390/nano9010079
|View full text |Cite
|
Sign up to set email alerts
|

Higher-Order Thermo-Elastic Analysis of FG-CNTRC Cylindrical Vessels Surrounded by a Pasternak Foundation

Abstract: This study analyses the two-dimensional thermo-elastic response of functionally graded carbon nanotube-reinforced composite (FG-CNTRC) cylindrical pressure vessels, by applying the third-order shear deformation theory (TSDT). The effective properties of FG-CNTRC cylindrical pressure vessels are computed for different patterns of reinforcement, according to the rule of mixture. The governing equations of the problem are derived from the principle of virtual works and are solved as a classical eigenproblem under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…The non-linear behavior of the shell structures under different loading conditions, makes the wave propagation problem particularly sensitive to the selected mechanical and geometrical parameters. This represents a key aspect of higher-order numerical approaches for shell structures [38][39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…The non-linear behavior of the shell structures under different loading conditions, makes the wave propagation problem particularly sensitive to the selected mechanical and geometrical parameters. This represents a key aspect of higher-order numerical approaches for shell structures [38][39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…Upon substitution of Equations (20), (21) into Equation (19), and by using the Lagrange's equations, we get the following relation:…”
Section: The Rayleigh-ritz Proceduresmentioning
confidence: 99%
“…Several experimental evidences in literature, have revealed that the behavior of micro-structures is size-dependent [2][3][4][5]. Thus, a large number of works has been recently published to conceive novel structural solutions, systems, and devices, while adopting different types of reinforcement phase, such as graphene nanoplatelets [6][7][8][9][10][11][12][13][14], or carbon nanotubes [15][16][17][18][19]. Among a large variety of numerical strategies, higher order theories represent the most useful tool for the investigation of the static and dynamic response of materials at different scales [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The functionally graded material (FGM) is a novel type of composite material whose mechanical properties smoothly and continuously vary in a preferred direction [11][12][13][14]. To better use the superior mechanical properties of carbon-based nanofillers and inspire from the concept of FGM, the functionally graded carbon nanotube-reinforced composite (FG-CNTRC) [15][16][17] and functionally graded graphene nanoplatelet reinforced composite (FG-GPLRC) [18][19][20] have been introduced, where the weight fractions of the CNTs and GPLs vary in the thickness direction.…”
Section: Introductionmentioning
confidence: 99%